Nutrition facts labels: who is actually reading them and does it help in meeting intake recommendations for nutrients of public health concern? - Maximilian Andreas Storz (BMC, 2023)
Abstract Background Fiber, potassium and calcium are nutrients of public health concern and their intakes in the United States are alarmingly low. The usage of nutrition facts labels has been reported to increase the odds for dietary reference intake of fiber in some studies. The overall evidence, however, is mixed, as some studies suggested that nutrition facts panels have little to no effect on average measures of diet quality. Here, we investigated whether the usage of nutrition facts labels was associated with meeting U.S. intake recommendations for three nutrients of public health concern: fiber, potassium and calcium. Methods We used cross-sectional multistage, stratified, clustered and probability sampling design data from the U.S. National Health and Nutrition Examination Surveys 2017-2020 cycle. The sample included 5,416 individuals aged 20 years or older, which may be extrapolated to represent 146,841,866 US Americans. Nutrient intakes were compared among individuals reading nutrition facts panels "frequently", "sometimes" or "rarely" using applied survey data analyses techniques (including multivariate logistic regression and marginsplots). Results We observed substantial sociodemographic differences between the three groups. Frequent readers were significantly more likely to be female and had higher educational levels. On average, they were also significantly older as compared to rare readers. Fiber intake in g/d was highest in frequent readers (17.09) and lowest in rare readers (14.64). The proportion of participants that met dietary fiber intake recommendations was almost four times higher in the frequent readers group (12.69%) as compared to the rare readers group (3.69%). In a bivariate logistic regression model, frequent label reading significantly increased the odds for meeting the fiber recommendations in Dietary Guidelines for Americans (OR: 2.15, p < 0.001). Rarely reading labels decreased the odds (OR: 0.57, p = 0.003). These odds remained essentially unchanged after adjusting for sociodemographic covariates, diabetes status and body mass index (OR: 1.84, p = 0.004; and OR: 0.62, p = 0.022). Conclusions Nutrition facts panel reading associates with fiber intake. Our findings have potential implications for public health nutrition strategies that may center around educational work.